Implementation of Hijab Business Strategy to Increase Sales and Consumer Loyalty in "Myluv.Hijab" in Wonogiri District - Yuniati, Rizka; Fuadi, Djalal (Proceedings International Conference on Education Innovation and Social Science, 2023)
This research intends to describe the the implementation of the myluv.hijab business strategy as well as the internal and external elements involved in the strategy's implementation. The qualitative case ethnographic design is used in this type of research. Techniques for gathering data include observation, documentation, and interviews. The data's validity was determined using method triangulation and source triangulation. The data analysis approach employs SWOT analysis during the data collecting phases of data reduction, data presentation, conclusion, and verification. According to the findings of this study, (1) S - O strategy: Improving product quality with clean stitches to fulfill rising market demand, particularly during Ramadan. W - O approach: using an excellent content marketing strategy to catch customers' attention, increase the dwindling number of TikTok watchers. S - T strategy: generating low-cost product improvements in order to reduce product design similarities with rivals. W - T strategy: attempting to enhance product supply by hiring competent seamstresses. (2) internal variables that comprise Strengths (strengths) and Weaknesses (weaknesses), with the first being Strengths (strengths): high product quality, friendly service, and product innovation. Second, flaws (flaws): low product stock and product delivery faults. External influences include Opportunities (opportunities) and Threats (threats), with the first being Opportunities (opportunities): increased market demand during Ramadan and collaboration with raw material suppliers for fabrics. Second, Threats (threats): fierce rivalry in the same hijab company, similar hijab designs among competitors, and a labor shortage in the sewing department.